THE PHYSICAL ASPECT OF THREE-DIMENSIONAL MIXED CONVECTION IN A UNIFORMLY HEATED HORIZONTAL PIPE (Sciences & Technology. A, exactes sciences, 2004)
This study concerns the numerical simulation of the three dimensional forced and mixed convectionheat transfer in a uniformly horizontal heated pipe. The complete Navier-Stokes equations arenumerically solved with a finite volume method.. The obtained results show that the mixed convectionflow is quite three-dimensional. As the Grashof number is increased, a secondary flow develops in theform of a two counter-rotating vortices. The vortices lead to a better mixing of the flow and thus enhancethe convective heat transfer: the local axial Nu decreases along an entrance region and then increasesdownstream instead of leveling off as in the case of forced convection. The increase is more important forhigher Richardson numbers